Technology transfer issue in the context of climate change: A critical exposition - Ansari, Abdul Haseeb (2013)

(untitled)
In order to successfully fight against the challenges posed by global warming, a phenomenon that is bringing menace to all, especially poor of the world, it is warranted that there should be a liberal attitude of developed countries towards transfer of technology, especially environmentally sound technology (ESTs), and transfer of financial resources from them to developing and least developed countries, and their capacity building so that developing and least developed countries could also be able to contribute to alleviate greenhouse gas (GHG) emissions. In spite of the fact that developed countries are mainly responsible for the phenomenon, they do not have enough political will to support these countries. They come out with one or the other excuses for not transferring ESTs. The current setback of the Eurozone economies might even have adverse impacts on it. The international IP regime provides for transfer of technology, but that has also fallen short of yielding encouraging results. In order to survive the world, the phenomenon of global warming has to be fought by all countries by means. In view of this, transfer of financial resources and transfer of technology is a must, even if the word ‘sustainable’ is substituted with the word ‘green’. The paper sheds light on these aspects and suggests that in order to facilitate transfer of technology, especially ESTs, the international IP regime should be liberalized by suitable amendments at international and national levels, and South-South cooperation should be augmented.